DISCOURSE ANALYSIS ON PHILOSOPHY FROM THE POINT O VIEW OF INTERACTIONAL SOCIOLINGUISTICS APPROACH - J Sutomo (Dinamika Bahasa dan Budaya, 2013)
Interactional sociolinguistics is anapproach to discourse analysis that has its origin in the search for replicablemethods of qualitative analysis that account for our ability to interpret whatparticipants intend to convey in everyday communicative practice. Methodologically,interactional sociolinguistics relies on close discourse analysis of audio- orvideo-recorded interaction. Such methodology is central to uncoveringmeaning-making processes because many conventions for signaling andinterpreting meaning in talk are fleeting, unconscious, and culturally variable.The purpose of this article is to analyzethe interactional patterns in casual conversation through which interactantsjointly construct social relations. This study, however, limits just the analysisof the grammatical patterns at the clause level which indicate power andsubordination within interaction. Theunderlying theories are Eggins’s Analyzing Casual Conversation – the grammar of casual conversation:enacting role relations. KEY WORDS: interactional sociolinguistics,communicative practice, interpreting meaning, interactants.